Asking the right questions: A stakeholder dialogue on generative AI in digital extension - Jones-Garcia, Eliot; Davis, Kristin E.; Singaraju, Niyati (International Food Policy Research Institute, 2025)
Generative artificial intelligence (gen AI) is gaining traction in agriculture. Conversational agents such as chatbots and voice assistants are being explored as digital extension solutions, promising scalable, personalized advice for farmers that can supplement and support the work of human extension agents. Yet designing and deploying such AI tools presents many challenges.